Knowledge and awareness of pediatricians about early interventions performed by pediatric dentists in the management of cleft lip and palate - A questionnaire-based study - Mansi Gandhy Baviskar; Shilpa Shetty Naik; Amil Joshi; Chinmaya Milind Chaudhary; Rachna Sharma; Aayushi Mehta (Wolters Kluwer Medknow Publications, 2024)
Background and Introduction: Cleft lip and palate (CL/P) is one of the most common congenital anomalies which require multidisciplinary care. Patients with CL/P require appropriate corrective treatment to improve health, function, and esthetics. Knowledge about the various treatment procedures available and the timing of the procedures among pediatricians is vital for them to refer the patient at the correct stage to the appropriate specialist for the best possible rehabilitation. Aim: The aim of this study was to evaluate the knowledge and awareness of pediatricians about early interventions performed by pediatric dentists in the management of CL/P. Materials and Methods: A closed-ended questionnaire that included questions regarding the knowledge and awareness of obturators, lip taping, and nasoalveolar moldings was formulated. A questionnaire with 20 questions was circulated among the pediatricians through a web-based portal. Their knowledge and awareness about early interventions performed by pediatric dentists in the management of CL/P were assessed. Results: Results showed that out of 323 pediatricians who participated in the survey, 99.4% had heard of obturators. Awareness about lip taping was 78.3% while that of nasoalveolar molding was 55.1%. The benefits of the procedure and appliance were not well known. Conclusion: To improve the health, psychological, and social support of patients with CL/P, more awareness needs to be created among pediatricians regarding the management to provide better and timely oral rehabilitation.